Using children’s digital picture books to teach disease preventive behaviors: A visual analysis of the Duma Says series - Esmeraldo Sarad; Charmen Cabatuan; Cleo Tionson; April Grace Subong (CV Rezki Media, 2026)
Background: During health emergencies such as the COVID-19 pandemic, children require accessible and developmentally appropriate resources to understand disease prevention and health-related behaviors. Children’s digital picture books have emerged as a promising medium for conveying public health messages through visual storytelling and age-appropriate narratives. Objectives: This study aimed to examine how children’s digital picture books represent disease preventive behaviors and moral values, using the Duma Says series as a case study. Methods: A qualitative visual and textual analysis was conducted on four digital picture books from the Duma Says Collector’s Edition. The study employed qualitative visual analysis and a critical discourse approach to examine representations of hygiene practices, social responsibility, and community engagement embedded in both images and narratives. Results: The findings indicate that the Duma Says series effectively integrates key COVID-19 preventive behaviors—such as handwashing, mask-wearing, social distancing, and sanitation—within child-friendly language and culturally contextualized visuals. In addition to promoting health practices, the books emphasize values of hope, responsibility, cooperation, and service, portraying children as active contributors to community well-being during a crisis. Conclusions: Children’s digital picture books, such as the Duma Says series, function as effective educational tools for promoting disease prevention awareness and values-based learning. Incorporating culturally grounded digital picture books into early childhood and health education may strengthen children’s health literacy, emotional resilience, and sense of social responsibility during public health emergencies.